Student’s Status in Contemporary Teaching: Problems and Perspectives - Arsić, Zvezdan M.; Babić Antić, Jelena B.; Radojević, Tatjana S. (Collection of Papers of the Faculty of Philosophy in Priština, 2019)
It is widely known that teaching as a social and historical category, during various periods of civilizational development, was characterized by several direct and specific factors, with the pupil (student) as a specific category. The status of the student in the process of teaching has been changing during the historical development of the society, which resulted in the change of their role. During the teaching process, the student is preparing for various roles in the society. Therefore, teaching should be in the function of accommodating conditions and enabling the student to participate in decision-making, to develop skills and habits, as well as to develop the ability for learning, thinking, remembering, problem solving, and intellectual independence, as well as the ability to use the gained knowledge in practice. Due to all the previously mentioned, main attention of this paper will be focused on comparative-critical and descriptive analysis of a student’s status and role in the historical development of teaching, with particular attention on the condition and problems in contemporary teaching.
Keywords: students’ role; students’ status; teacher; student; teaching